A Model for People-Centric Software Configuration Management - Fahmy, Syahrul; Deraman, Aziz; Yahaya, Jamaiah H.; Ngah, Amir; Salman, Fouad Abdulameer (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Software Configuration Management (SCM) is the adaptation of Configuration Management in software engineering to control changes to software products. Its implementation is guided by international standards and procedures, in addition to an array of supporting tools. However, the issues of project delays and products that do not fit its purpose still prevail in software development, questioning the practice of SCM by software organizations. Current research efforts in are mainly focused on technical issues, with little interest (if any) in the role of human in SCM implementation. This paper proposes an alternative view of SCM, which emphasizes the role of human in its implementation. The People-Centric Software Configuration Management (P-SCM) model comprises of four components namely People, Process, Tools and Documentation. It reveals the competency of the software project team, extensiveness of activities carried out by the organization, availability of supporting tools, and comprehensiveness of documentation. PSCM supports software organizations in decision-making activities, provide insights to project discrepancies, identify best practices and pitfalls, support the identification of training needs and the selection of tools. Initial results reveal that P-SCM provides additional input to software organizations in project planning and outsourcing activities.